Presbyterians in Ireland Identity in the Twenty-First Century - Baillie, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Does the Presbyterian church help or hinder individuals in their lives? Baillie uses over a hundred interviews with Ministers and individuals to examine the role of women, the influence of life history and geographical location, education, inter-church relations, the Orange Order, Freemasonry, the ministry and the future.
Keywords: Religion and sociology; Political communication; Cultural studies; Protestantism; Sociology of Religion; Political Communication; Cultural Studies; Protestantism and Lutheranism; Social Aspects of Religion